I understand. In that case, what's wrong with 1.2.22? Let $\overrightarrow{AB} = x$ and $\overrightarrow{AC} = y$. Clearly $x$ and $y$ are not parallel, so by 1.2.20. (b), $bx + ay$ bisects the angle between $x$ and $y$. Since $\overrightarrow{AD}$ also bisects the angle between $x$ and $y$, it follows that $\overrightarrow{AD} = t(bx + ay)$ for some $t \in \mathbb{R}$.
Then $\overrightarrow{AD} = \overrightarrow{AP} + \overrightarrow{PD}$, but notice that $\triangle PBD \sim \triangle ABC$, so $\overrightarrow{AD} = s(x + y)$ for some $s \in \mathbb{R}$. Then by 1.1.10. (b), we must have t…